Foreign experience of effective energy conservation management of industrial enterprises - Tytarchuk, Dmytro (Management and Entrepreneurship: Trends of Development, 2018)
The relevance of the research is determined by the fact that the reason of high energy intensity of industry in Ukraine are the significant technological lag of most branches of the economy as apposed to the level of developed countries, the unsatisfactory sectoral structure of the national economy, which objectively limits the competitiveness of production and pulls down the economy, especially in the conditions of its external energy dependence. Market principles of energy use encourage domestic producers to look for new ways of enterprise development. The implementation of effective energy-saving management at industrial enterprises provides an opportunity to increase energy efficiency, reduce negative environmental impacts, take the leading positions both at domestic and international market. The subject of the research is the methodological aspects of efficiency of the implementation the energy-saving management in foreign countries. Purpose. The goal of the research is to study the experience of foreign countries in the field of efficient use of energy resources, as well as to identify ways to improve energy-saving management at industrial enterprises. Design/methodology/approach. The basic principles of the research are the principles of causality and objectivity, system-defined and comparative methods, institutional and structural-functional approach have been used. Findings. As a conclusion, suggestions for energy efficiency of industrial enterprises are proposed in the article. Research limitations/implications. The scientific consequence of the research is analysis of the actions of foreign countries in the energy sector, which have determined the speed and scale of the implementation of energy-saving measures at industrial enterprises. Originality/value. In practice, this will help to increase the competitiveness of Ukrainian enterprises through effective energy-saving management, increase their productivity, avoid losses from acquisition of energy resources, increase financial support for the development of domestic innovative technologies, reduce the environmental burden to the environment and lead to the introduction of energy-saving measures at industrial enterprises.